Prognosis of immune checkpoint inhibitor-induced myasthenia gravis: a single center experience and systematic review - Qin, Yuhui; Chen, Siyuan; Gui, Qian; Zhang, Teng; Li, Yanan; Du, Zhijuan; Lv, Yahui; Du, Xiangyu; Hu, Yi; Liu, Zhefeng (Frontiers in Neurology, 2024)
Background: Immune checkpoint inhibitors (ICI)-induced myasthenia gravis (MG) is an uncommon but potentially fatal neurotoxicity. We aim to help physicians familiarize themselves with the clinical characteristics of ICI-induced MG, facilitating early diagnosis and prompt intervention. Methods: We searched the Chinese People's Liberation Army General Hospital medical record system from January 2017 to August 2023 for patients diagnosed with ICI-induced MG. We systematically reviewed the literature until August 2023 to identify all similar patients. We collected clinical information on these patients. Results: 110 patients were identified, 9 from our institution and 101 from case reports. In our institution, Median age was 66 years (range: 49-79 years). 6 were males. The most common was lung cancer (n = 4). All patients had no previous history of MG and received PD-1 or PD-L1 inhibitors. The median time from ICI initiation to first MG symptoms was 4 weeks (range: 2-15 weeks). ICIs were discontinued in all patients. Most patients initially received high-dose corticosteroids, and their symptoms improved. Some patients are discharged with corticosteroids maintenance therapy. In addition, 55 patients (50%) with concomitant myositis and/or myocarditis and MG-induced mortality were more common in the myositis and/or myocarditis group (10.9% vs. 34.5%, p = 0.016). Overlap of myositis with MG (OR = 3.148, p = 0.009) and anti-AChR antibody positivity (OR = 3.364, p = 0.005) were both significantly associated with poor outcomes. Conclusions: Our study reveals the prognosis of ICI-induced MG and suggests that myositis and/or myocarditis are severe comorbidities of ICI-induced MG, emphasizing the importance of early diagnosis and clinical intervention.